2018
DOI: 10.1186/s12890-018-0715-4
|View full text |Cite
|
Sign up to set email alerts
|

Regional heterogeneity in response of airway epithelial cells to cigarette smoke

Abstract: BackgroundCigarette smoke (CS) exposure causes an abnormal inflammatory response, which can result in chronic obstructive pulmonary disease (COPD). Previous studies show that this disorder predominantly occurs in peripheral or small-airway areas, whereas the same condition has not been identified in the larger airways during the course of COPD. However, the different biochemical and genetic alterations occurring in response to CS exposure among airway epithelial cells from different sites in the lungs have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Direct comparisons of Aspergillus fate in A549 and 16HBE cell lines have not been previously addressed (for review [70]), despite differential activation with lipopolysaccharide [46], Fusobacterium [71], glucocorticoids [72] and cigarette smoke [73] exposure. Overall, 16HBE cells were able to take up the A. fumigatus strains ∆pksp and ∆rodA more efficiently than A549, which may be linked with increased expression of mucus on the epithelia [74].…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparisons of Aspergillus fate in A549 and 16HBE cell lines have not been previously addressed (for review [70]), despite differential activation with lipopolysaccharide [46], Fusobacterium [71], glucocorticoids [72] and cigarette smoke [73] exposure. Overall, 16HBE cells were able to take up the A. fumigatus strains ∆pksp and ∆rodA more efficiently than A549, which may be linked with increased expression of mucus on the epithelia [74].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the pulmonary clearance of inhaled [ 99 m Tc] methoxyisobutyl isonitrile ([ 99 m Tc] sestamibi), a radiolabeled MRP1 substrate, has been recorded to decrease in smokers and the decrement was attributed to modulation in MRP1 activity and expression profile ( Mohan et al, 2019 ). The distal lung epithelium has been reported to be the initial site of development of tobacco smoke-induced diseases such as COPD ( Baskoro et al, 2018 ). Thus, we investigated the potential impact of CSE on MRP1 activity and/or abundance in human AT1-like and NCI-H441 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The different type of airway epithelia cells and cigarette smoke sources could be responsible for the differences in our results. For example, Baskoro demonstrated that SAE cells exhibit a different proinflammatory response to cigarette smoke exposure compared to HBEs [49].…”
Section: Discussionmentioning
confidence: 99%